Nineteenth-Century Burial Reform in England: A Reappraisal - Julie Rugg (Histoire, Médecine et Santé, 2021)
In comparison with other European nations, 19th-century burial reform in England is often related as a history of difference and failure. England lacked centralising legislation to enforce the establishment of new, sanitary cemeteries. Rather, permissive regulation encouraged the creation of new cemeteries, largely reliant on local initiative. This paper presents a re-evaluation of that history by focussing on archival documents from the General Board of Health and local burial board minutes. The paper discusses the way in which key individuals and agencies developed a refined understanding of the sanitary dangers presented by decomposing bodies. This understanding rested on deep familiarity with Continental European research and practices. Despite the lack of centralising legislation, the General Board of Health and the Burial Office administered an effective system of sanitary burial governance which combined inspection, advice and bureaucratic processes that worked with local communities to develop a national network of cemeteries that were managed according to scientific practices.